Biodegradable coordination polymer: Polycondensation of glutaraldehyde and starch in complex formation with transition metals Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) - Nahid Nishat; Ashraf Malik (Arabian Journal of Chemistry, 2016)
Starch a biopolymer, possesses many unique characteristics features accompanied with some shortcoming simultaneously. Some synthetic compounds are of great help to these demerits of starch and so by an addition of all these alternatively may acquire the tailor made features of starch-based compounds. By combining the individual advantages of starch and some other compounds and elements, starch-based biodegradable polymers were prepared for potential applications in biomedical and environmental fields. In this research, the structural analysis and characterization studies of starch glutaraldehyde polycondensed polymer were undertaken, and then the formation of polymer metal complexes with transition metal in coordinated form are carried out. FT-IR spectroscopy and 1H NMR and 13C NMR spectroscopy were used to analyze the functionality of the synthesized compound. CHN of the synthesized compound was supported by FT-IR and NMR which again proved helpful for structural analysis. Electronic spectroscopy confirmed the geometry of the synthesized compounds. Thermal studies were carried out by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Besides this the biodegradable studies were carried out by ASTM standards of biodegradable materials by CO2 evolution in respirometric titration method. All the polymers showed good thermal strength and reduced biodegradation on attachment of transition metals, Mn(II), Co(II), Ni(II), Cu(II) and Zn(II).